Examining Students’ Epistemological Views of Engineering among First Year Engineering Students - Yang, Yang (My University, 2019)
This is a complete research paper. The research interest in engineering epistemology is growing as more engineering education researchers consider that students’ beliefs about the nature of engineering is essential to how they learn, which influences their professional preparation [1]. Epistemology refers to how individuals view the nature of knowledge and knowing in a particular domain, in this case, engineering [2].